Public perceptions and influencing factors of seasonal influenza vaccine uptake in Makkah region, Saudi Arabia: a cross-sectional study - Alharthi, Mohammed S.; Alshehri, Abdullah A.; Baali, Fahad H.; Altuwairqi, Nawaf Awd; Altalhi, Meshari Hassan; Almalki, Rayan Azib; Aljuaid, Meshal Khalid; Algarni, Majed A.; Alzahrani, Mohmmed S.; Alorfi, Nasser M.; Alruqayb, Wadia S. (Frontiers in Public Health, 2025)
BackgroundSeasonal influenza vaccination is essential for reducing the risk and impact of influenza. Makkah region in Saudi Arabia, a destination for millions of pilgrims during Hajj and Umrah, presents a unique context for this study. Therefore, this research investigates the prevalence and influencing factors of influenza vaccine uptake among the public in Makkah region, Saudi Arabia.MethodThis cross-sectional study was conducted in Saudi Arabia between February and June 2024. The main researcher developed the questionnaire, which was reviewed by five academics and then piloted with 20 individuals for validation. An online questionnaire was used, targeting residents aged 18 and over with internet access. A snowball sampling method was applied. Data were collected via Google Forms and analyzed using SPSS version 26, employing descriptive statistics such as frequencies, percentages, and means.ResultsThe total number of respondents is 450 participants, with a response rate of 4.5%. Most respondents were male (71.1%) and aged between 18 and 30 years (44.5%). Education levels varied, with 57.5% holding a bachelor’s degree. Vaccination uptake showed 65.1% had received the vaccine, with 31.1% confident it is safe. Despite this, 58.8% did not get vaccinated this season. Confidence in the vaccine’s effectiveness was 59.5%, though 41.2% reported breakthrough infections. Accessibility was generally rated easy (57.7%). Social pressure (17.4%), trust in health institutions (36.9%), and COVID-19 concerns (36.7%) significantly influenced vaccination decisions. The likelihood of vaccination next season displayed polarized views.ConclusionThis study provides significant insights about vaccine hesitancy that may inform future research endeavors and practical applications. Understanding the various factors that impact the adoption of influenza vaccines offers valuable insights for developing targeted interventions and public health policies to improve vaccination rates. This study enhances theoretical understanding and practical strategies to encourage influenza vaccination, thereby improving public health initiatives in the area and beyond.